A Comparative Analysis of Verbal and Non-Verbal Communication in Classroom Interaction across English and Urdu in Pakistani Academic Context - Siddiqua Bibi (ACADEMIA International Journal for Social Sciences, 2025)
Interaction in the classroom is a complicated process that includes both spoken and unspoken communication. While non-verbal communication comprises posture, tone of voice, eye contact, facial expressions, and gestures, verbal communication includes spoken words such as inquiries, answers, and explanations. For teaching and learning to be effective, both types are essential. This study compares the verbal and nonverbal communication in Pakistani universities that are taught in Urdu and English. Using a mixed-methods research approach, 80 university students were given a questionnaire to complete, which yielded quantitative data in addition to qualitative classroom observations. The results show that while Urdu classrooms use more expressive nonverbal clues and flexible verbal strategies, English classrooms rely more on structured verbal communication with few nonverbal expressions. The study highlights the importance of understanding linguistic and cultural differences in classroom communication to improve teaching practices and learner engagement.